Hereditary transthyretin amyloidosis: a comprehensive review with a focus on peripheral neuropathy - Poli, Loris; Labella, Beatrice; Cotti Piccinelli, Stefano; Caria, Filomena; Risi, Barbara; Damioli, Simona; Padovani, Alessandro; Filosto, Massimiliano (Frontiers in Neurology, 2023)
Amyloidoses represent a group of diseases characterized by the pathological accumulation in the extracellular area of insoluble misfolded protein material called “amyloid”. The damage to the tissue organization and the direct toxicity of the amyloidogenic substrates induce progressive dysfunctions in the organs involved. They are usually multisystem diseases involving several vital organs, such as the peripheral nerves, heart, kidneys, gastrointestinal tract, liver, skin, and eyes. Transthyretin amyloidosis (ATTR) is related to abnormalities of transthyretin (TTR), a protein that acts as a transporter of thyroxine and retinol and is produced predominantly in the liver. ATTR is classified as hereditary (ATTRv) and wild type (ATTRwt). ATTRv is a severe systemic disease of adults caused by mutations in the TTR gene and transmitted in an autosomal dominant manner with incomplete penetrance. Some pathogenic variants in TTR are preferentially associated with a neurological phenotype (progressive peripheral sensorimotor polyneuropathy); others are more frequently associated with restrictive heart failure. However, many mutations express a mixed phenotype with neurological and cardiological involvement. ATTRv is now a treatable disease. A timely and definite diagnosis is essential in view of the availability of effective therapies that have revolutionized the management of affected patients. The purpose of this review is to familiarize the clinician with the disease and with the correct diagnostic pathways in order to obtain an early diagnosis and, consequently, the possibility of an adequate treatment.